An outbreak of East Coast Fever in a herd of Sanga cattle in Lutale, Central Province of Zambia - Minjauw, B.; Otte, M.J.; James, A.D.; Castro, J.J. de; Permin, A.; Giulio, Giuseppe di (Elsevier, 1998)
An outbreak of East Coast fever (ECF) occurred in an experimental herd of Sanga cattle maintained under a traditional rangeland grazing system at Lutale, Central Province of Zambia. Two groups of cattle had been kept under different tick-control regimes for several years prior to the introduction of the disease and epidemiological information on the outbreak were recorded. Weekly tick control was not sufficient to achieve full protection against Theileria parva infection. Systematic body temperature monitoring seems to be a good method for early detection of infection resulting in an important reduction of the case fatality rate after treatment with anti-theilerial drugs.